RATR of adaptive angular-sector segmentation based on grey incidence analysis model. Issue 1 (6th February 2017) - Xiao, Yongsheng; Huang, Lizhen; Zhou, Jianjiang
Abstract : Purpose: The purpose of this paper is to solve the azimuth sensitivity of a high-resolution range profile (HRRP), which is one of the biggest obstacles faced by a radar automatic target recognition (RATR) system. Design/methodology/approach: Aimed at addressing the shortcomings of the equal angular-sector segmentation based on the scatterer model, an adaptive angular-sector segmentation is proposed on the basis of grey incidence analysis (GIA). Findings: The main conclusions reached are as follows. First, the adaptive angular-sector segmentation in terms of GIA is suitable for RATR based on the HRRP; and, second, the adaptive angular-sector segmentation based on the type-B degree of grey incidence model is better than the Deng-Si degree of grey incidence model and the degree of grey slope incidence model. Practical implications: The outcome obtained in this paper can be selected for the RATR application. Originality/value: This paper has been built on the basis of previous research achievements, and a new RATR method of adaptive angular-sector segmentation is presented based on the GIA.